The Effect of Queen Cell Size Difference in Morphometrics of Bees Queen Apis cerana - Sri Minarti; Arga Rama Yusryansyah; Dewi Masyithoh (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The purpose of the study is to know the influence of Queen Cell’s queen on body length, weight, and length of the wing of the ApisCerana bee. The material used is the larvae of honey bees, honey, royal jelly, and queen's cells. The method used was a trial using a completely random design with three treatments in each with five repeats. The tested treatment is Queen Cell with small, medium, and large sizes. The variable measured is body length, weight, and the length of the queen bee wing. Data analyzed using variance analysis or ANOVA, and if there is a significant effect it will be continued with the double distance test of Duncan. The results showed that the different Queen Cell treatment gives a very significant effect (P < 0.01) on each body weight with an average value is 57,30 ± 8,30; 68,20 ± 5,41 and 81,00 ± 7,42 mg, but on length of the body, length of wings and width of thoracic do not give significant effect (P > 0,05). The average value of the consecutive body length is12,43 ± 0,41; 12,57 ± 0,09 dan 12,28 ± 0,18 mm, the average value of the consecutive wings is 8,48 ± 0,29; 8,67 ± 0,17 and 8,74 ± 0,17 mm while the average result of the thoracic width size is 4.04 ± 0.11, 4.14  ±  0.05 and 4.22 ± 0.39 mm